An Analysis of Consumer Preference of Coffee Attributes: The Case Consumers of Local SME’s Coffee Shop Jakarta Greater Area - Heriyati, Pantri; Sanny , Lim; Kelana, Beny Widarman Bin Yus (International Journal of Psychosocial Rehabilitation, 2020)
With the increasing number of coffee shop and popularity of coffee and drinking coffee among Indonesian people, this study aims to determine consumer preferences for the attributes of coffee drinks and attributes of consumer considerations for buying coffee in local coffee shop run by SME’s. This study used quantitative approach. Since the population of coffee drinkers in greater area Jakarta is indefinite, therefore this research employed non-probability sampling with quota random sampling method. The respondents are selected based on criteria coffee drinker lived in Jakarta who experienced drinking coffee Data were analysed using statistic descriptive. Based on the results of a study of 100 respondents (consumers of coffee drinks) and Likert scale calculation rules for attributes on sub-variables of product characteristics, namely: coffee taste, coffee aroma, serving presentation, serving size, coffee origin (local vs. imported), brand image of coffee shop, and positive feeling about the coffee, showing a total score (TS) of 3232. The highest score is 4000, so the proportion of score (PS) amounting to 80.8% (obtained from calculations 3232/4000 x 100%). This can be interpreted that the consumer’s preference for all the attributes that exist in coffee beverage products in the coffee shop in the category of like very much. This means that most respondents like coffee drinks very much. Based on the index of value of coffee attributes, it is found that the highest score is the aroma of coffee, the second highest score is for taste, the third is the attribute of coffee origin, following by the fourth highest score which is brand image coffee shop. The fifth highest score is the (positive) feeling aspect or feeling. The sixth highest score is the size of the serving, and serving presentation positioned seventh, and lastly is the store promotion. This finding implies that the respondent’s preference over coffee and drinking coffee developed based on value criteria. From the eight attributes that were measured; coffee aroma, taste and origin were the three most important attribute of customer preference. These finding give important insight for managerial and business practice to emphasize their strategic orientation and resource allocation to develop that specific areas. This study has not been able to develop comparison between local coffee shop brand and coffee originality (local vs. imported), which it may reveal more robust finding implication on how shop brand may influence the customer preference over coffee. This research contributes to theory and practice in providing method and empirical evidence of how to measure, calculate and rank attributes of consumer coffee preference which are still limited conducted in previous studies in related topic